Strategi Kepala Sekolah Dalam Membentuk Kecerdasan Spiritual Melalui Habitual Curriculum Pembelajaran Al Quran - Khusnia, Alfun; Fadhilatunnisa, Fadhilatunnisa; Suherman, Suherman (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2023)
In the modern world, technology is rapidly advancing. To protect themselves from the negative effects of technological advancements and social media, students are required to have spiritual intelligence. Spiritual intelligence cannot be achieved instantly. It requires support from the surrounding environment and habitual practices in daily activities. This research aims to determine the strategies of school principals in shaping students' spiritual intelligence through Quranic learning. The research method used is qualitative research with a descriptive approach. The research subjects include the School Principal, Islamic Education (PAI) Teachers, six students, and three parents of students from MI Pembangunan UIN Jakarta. Data collection techniques include field observations, interviews, and documentation. The results of the research show that the strategies of school principals in shaping students' spiritual intelligence through Quranic learning involve implementing programs such as the Habitual Curriculum, which includes Quran recitation (tadarus), Quran memorization (tahfidz), Quranic education center (TPA), and completion of the Quran (Khotmul Qur'an). From the interviews and observations, it was found that these programs empirically enhance spiritual intelligence, with students consistently demonstrating qualities such as honesty, flexibility, gratitude, trustworthiness, patience, and concern for the environment.